2018
DOI: 10.1165/rcmb.2017-0083oc
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Depletion Impairs Host Defense to Pulmonary Infection with Pseudomonas aeruginosa in Mice

Abstract: Platelets have been implicated in pulmonary inflammatory cell recruitment after exposure to allergic and nonallergic stimuli, but little is known about the role of platelets in response to pulmonary infection with Pseudomonas aeruginosa. In this study, we have investigated the impact of the experimental depletion of circulating platelets on a range of inflammatory and bacterial parameters, and their subsequent impact on mortality in a murine model of pulmonary infection with P. aeruginosa. P. aeruginosa infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 41 publications
6
44
1
Order By: Relevance
“…These findings support the notion that thrombocytes participate in the early immunological response to agents in the circulation [55]. This has been suggested to result from thrombocytes participating in the recruitment of neutrophils [56] and in the activation of neutrophils to release neutrophil extracellular traps (NETs) [57]. In Gram-negative sepsis with E. coli, NETs are induced by activation of TLR-4 on thrombocytes, that subsequently activates neutrophils via CD11a [58].…”
Section: Discussionsupporting
confidence: 79%
“…These findings support the notion that thrombocytes participate in the early immunological response to agents in the circulation [55]. This has been suggested to result from thrombocytes participating in the recruitment of neutrophils [56] and in the activation of neutrophils to release neutrophil extracellular traps (NETs) [57]. In Gram-negative sepsis with E. coli, NETs are induced by activation of TLR-4 on thrombocytes, that subsequently activates neutrophils via CD11a [58].…”
Section: Discussionsupporting
confidence: 79%
“…Platelets are protective against intravenous Staphylococcus aureus infection, and thrombocytopenic mice have a higher kidney bacterial burden in a DT model of thrombocytopenia [35]. In an antibody-mediated model of thrombocytopenia, mice were vulnerable to pulmonary Pseudomonas aeruginosa infection, which is coincident with higher bacterial lung CFUs [36]. Our results extend these prior studies to a medically relevant fungal pathogen.…”
Section: Discussionsupporting
confidence: 78%
“…Although recent studies have shown that the absence of platelets impairs host defense against chronic P . aeruginosa infection[ 45 ], the immune regulatory mechanisms of platelets are not fully understood. In this study, we identified the critical role of platelets in host defense against P .…”
Section: Discussionmentioning
confidence: 99%
“…aeruginosa infection in an acute infection model. In contrast to chronic infection[ 45 ], the platelets were activated in acute infection site, and the number of platelets in blood circulation was also significantly increased during P . aeruginosa lung infection.…”
Section: Discussionmentioning
confidence: 99%